The Role of the Environmental Management System in The Integrated Management System Of Companies (Eurasian Research Bulletin, 2022)
In this article, was characterized the environmental management system. The role of EMS in the integrated management system was shown. The scope of the EMS and the quality management system at the enterprise are clearly presented. Considered and substantiated are the advantages obtained by the enterprise in the implementation of the EMS along with the QMS.